Bangladesh's Labour Migration Practices: Government's Unjustified Priority for Out-Migrants (Expatriates) rather than Pre- and Post-Migrants – An Analytical Study Over Cumilla, Bangladesh - A. Z. M. Shoeb; Yasir Jawwad Shoeb; Enamul Huq, Md. (GEOGRAFI, 2024)
The objective of the article is to refine and shape the government policy of Bangladesh so that the country can exist in the competitive world labour market and earn much foreign remittances. This article would find out the ideal attitudes and policies for the three categories of migrants: pre-migrants, out-migrants and post-migrants for the consideration of the concerned ministry of Bangladesh. For this article, empirical data has been collected from the survey area. This survey was conducted over Chandina Upazila of Cumilla district in August, 2019 through a structured questionnaire. This paper will investigate the capabilities and backgrounds of those three categories of migrants on seven criteria: age, education, language-efficiency, trade-skills, bank account experience, familiarity with insurance policy and leave-before profession at place of origin. Then the data-set has been input in the SPSS programme for analysis. Due to the government policies regarding labour migration at the place of destination, e.g. Gulf States, the three categories of migrants are significantly influenced. As the government, surprisingly, has no minimum ceiling of education and age for probable male migrants abroad, the pre-migrant category is not encouraged to enrich their minimum literacy and hardly wait for maturity up to 21 years of age fixed by the government. Henceforth, the successful out-migrants are mostly teen-agers, less educated, and unskilled. Moreover, as per government policy, the post-migrant category is not cared much after coming back from abroad and this category cannot settle down smoothly with their money and foreign experience. In means that the government gives utmost importance to out-migrants, a little for post-migrants and a very little for pre-migrant categories. How ever, the pre-migration scenarios take place earlier than out-migration or post-migration.  The article could show the government how to set up acceptable criteria by which pre-migrants would feel pressure to become educated and skilled before overseas employment. Due to efficient policies, a huge number of less-skilled and unskilled labourers will have become unable to migrate and the more literate cum skilled people will be able to come in the front-line for overseas migration. The contribution of the study is two folds. First, it contributes to improve policy making of the Bangladesh government by giving equal importance for all the three categories of migrants or the best one is to give much priority to the pre-migrants and second, to post-migrants and out-migrants.